Experiment in Associating Gram panchayats with Forest Management in Bihar - Sinha, J. N. (Indian Forester, 1959)
"Forest is an unlocked property spread over the landscape. For its due conservation active co-operation of the local people is a condition precedent. It is specially so in respect of the Community Forests, that is to say, forests occurring in between or in the vicinity of villages. In the existing conditions of orthodox management there are in effect two parties - one Government, in control of the forest ; the other, the local people, suspecting and resenting the control and perpetually trying to outwit the first party. The result is that Community Forests are not being properly protected and there are also embarrassing complaints bred from misunderstanding and suspicion. The lower forest staff have also opportunities of temptation. The only logical way is to merge the two parties by associating Panchayats with management of the Community Forests and to create among the people a feeling of belonging towards the forest. At present the local people are allowed to take from the annual coupes, free of charge, all that they may need for their personal consumption, still they do not regard the forest as their own.